PEMANFAATAN BATANG PISANG DAN BEKATUL DENGAN KONSORSIA BAKTERI INDIGEN LCN (LIMBAH CAIR NANAS) UNTUK PAKAN TERNAK RUMINANSIA - Melinda Marta Ningtyas; Hening Widowati; Achyani Achyani (BIOLOVA, 2020)
Abstract: Ruminant feed consists of banana stems and rice bran as a concentrate. Banana stems containnutrients including dry matter (BK) 9.8%, total ash 18.4%, crude fat (LK) 3.2%, crude fiber (SK) 31.7%,and crude protein (PK) 8 8%. And rice bran contains protein 13.11 - 17.19 percent, fat 2.52 - 5.05 percent,carbohydrates 67.58 - 72.74 percent, and crude fiber 370.91 - 387.3 calories and rich in vitamin B,especially vitamin B1 (thiamin).The fermentation process uses a konsorsia bacteria indigen LCN so that thefeed is more easily absorbed by ruminant.